Greener solvents in extraction of proteins and peptides - Katarína Maráková (Advances in Sample Preparation)
The sample pretreatment still represents a fundamental aspect of any analytical workflow, and the implementation of sustainable and efficient extraction of proteins is essential to satisfy the increasing requirements for high-quality extraction of proteins from their natural sources. Proteins, with their unique structural and functional characteristics, are utilized in several industries such as pharmaceuticals, biomedicine, cosmetics, and food. Traditional methods for protein extraction depend predominantly on hazardous organic solvents, thereby presenting both environmental and health-related risks. Recent progress has been directed towards developing environmentally benign alternative extraction approaches. Ionic liquids and deep eutectic solvents have demonstrated in the recent decade great potential as green solvents for protein extraction, thanks to their tunable properties that can be customized to various extraction protocols; thus, they are characterized by high selectivity. At the same time, they usually cause minimal denaturation of proteins, which is essential for normal functioning of proteins. However, the industrial implementation of these solvents still encounters obstacles, such as the knowledge gaps about their solvating characteristics, complexity in their synthesis (especially for ionic liquids), and potential for their reusability. The present review paper deals with the recent advances in the extraction of proteins and peptides with ionic liquids and deep eutectic solvents, discusses the influence of solvent characteristics on the extraction process, describes various extraction methods, and presents prospective future directions in this field.